Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fpsyt.2022.1072380
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 and TNF-β: Predictive biomarkers for transition to psychosis in ultra-high risk individuals

Abstract: BackgroundDysregulation of immunity, such as levels of inflammatory factors, has been regarded as a sign of schizophrenia. Changes in cytokine levels are not only described in the early onset of disease, but also observed in ultra-high risk (UHR) individuals. This study aimed to investigate the potential of cytokines as biomarkers for psychotic disorders and in individuals at UHR of developing a psychotic disorder in the future.MethodsThe Luminex liquid chip technology was used to detect the concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 79 publications
2
7
0
Order By: Relevance
“…Likely in the prodromal and active phases of schizophrenia, an activation of the innate immune response predominates with greater activation of neutrophils, while in the residual phases, when negative symptoms are Likely in the prodromal and active phases of schizophrenia, an activation of the innate immune response predominates with greater activation of neutrophils, while in the residual phases, when negative symptoms are prevalent, activation of lymphocytes, typical of the adaptive immune response, would be prevalent.Following what has been reported in our study, it was observed that a high blood concentration of Interleukin-17 (IL-17), which stimulates neutrophil proliferation [48], was found in rst-episode psychotic patients [49].…”
Section: Discussionsupporting
confidence: 80%
“…Likely in the prodromal and active phases of schizophrenia, an activation of the innate immune response predominates with greater activation of neutrophils, while in the residual phases, when negative symptoms are Likely in the prodromal and active phases of schizophrenia, an activation of the innate immune response predominates with greater activation of neutrophils, while in the residual phases, when negative symptoms are prevalent, activation of lymphocytes, typical of the adaptive immune response, would be prevalent.Following what has been reported in our study, it was observed that a high blood concentration of Interleukin-17 (IL-17), which stimulates neutrophil proliferation [48], was found in rst-episode psychotic patients [49].…”
Section: Discussionsupporting
confidence: 80%
“…Likely in the prodromal and active phases of schizophrenia, an activation of the innate immune response predominates with greater activation of neutrophils, while in the residual phases, when negative symptoms are prevalent, activation of lymphocytes, typical of the adaptive immune response, would be prevalent. Following what has been reported in our study, it was observed that a high blood concentration of Interleukin-17 (IL-17), which stimulates neutrophil proliferation [ 48 ], was found in first-episode psychotic patients [ 49 ].…”
Section: Discussionsupporting
confidence: 65%
“…TNFβ/Lymphotoxin-α is a cytokine expressed by lymphocytes and it was decreased in the FEP samples, as was the protein Flt3L. TNFβ was recently shown to be increased in a subgroup of high-risk individuals for schizophrenia in a Chinese population using an enzyme-linked immunosorbent assay [37]. Future studies with larger patient groups and of different ethnicity are required to support the role of TNFβ in acute and chronic schizophrenia patients.…”
Section: Discussionmentioning
confidence: 99%